Scratch-resistant PC material and preparation method thereof
By adding SAN rigid organic particles and modified nano MgO to PC/ABS materials, combined with high-speed mixing and twin-screw extrusion technology, the problem of poor scratch resistance of PC/ABS blends is solved, and the scraping resistance of the material is achieved Improvement of rubbing, strength and toughness, suitable for large-scale industrial production.
Patent Information
- Application Number
- CN202411432355.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2024-12-20
AI Technical Summary
The existing PC/ABS blends have poor scratch resistance, which is limited by the compatibility of ABS and PC and the low surface hardness.
Using the combination of PC resin, ABS resin, SAN rigid organic particles and modified nano MgO, the scratch-resistant PC material was prepared through high-speed mixing and twin-screw extruder process, and the modified nano MgO was treated with a silane coupling agent. Reinforced material compatibility and interface combination.
It significantly improves the scratch resistance, strength and toughness of the material, improves the wear mechanism for fatigue wear, enhances the compatibility and interface combination of the material, and improves production efficiency and cost-effectiveness.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a scratch-resistant PC material and a preparation method thereof. Background Art
[0002] PC resin, or polycarbonate, is an engineering plastic with excellent performance. Due to its excellent impact resistance, heat resistance, dimensional stability, creep resistance and good transparency, it is widely used in the fields of automobiles, electronic appliances, optical components, etc. The most outstanding feature is its light transmittance. The light transmittance of polycarbonate is as high as 90% at a thickness of 1mm, and its refractive index is high. It has a wide range of application value in the field of optical components. However, polycarbonate has poor scratch resistance and low surface hardness, which limits the application of the material. ABS resin (acrylonitrile-styrene-butadiene copolymer) is a thermoplastic polymer material structure with high strength, good toughness and easy processing and molding.
[0003] PC and ABS are two engineering plastics with excellent performance. The engineering plastic mixture of the two, PC / ABS, is a thermoplastic plastic made of polycarbonate PC and acrylonitrile-styrene-butadiene copolymer ABS alloy. It combines the excellent performance of the two materials, the formability of ABS material and the mechanical and impact properties of PC. It can be widely used in alloy furniture, home appliances, outdoor products, communication equipment, electronics industry and other fields.
[0004] However, the current performance of PC and ABS blends is often limited by the poor compatibility between ABS and PC; at the same time, the scratch resistance of PC / ABS alloys is not good. Summary of the invention
[0005] In order to overcome the deficiencies of the prior art, the object of the present invention is to provide a scratch-resistant PC material, which has excellent scratch resistance as well as excellent strength and toughness.
[0006] Another object of the present invention is to provide a method for preparing a scratch-resistant PC material, which has simple process, convenient operation and control, stable quality, high production efficiency, low production cost, and is suitable for large-scale industrial production.
[0007] The purpose of the present invention can be achieved by the following technical solutions:
[0008] A scratch-resistant PC material, characterized by comprising the following raw materials in parts by weight:
[0009] PC resin: 80 parts,
[0010] ABS resin: 5-15 parts,
[0011] SAN rigid organic particles: 10-20 parts,
[0012] Modified nano-MgO: 3-7 parts.
[0013] Furthermore, the PC resin is a bisphenol A polycarbonate resin, and its melt index at 300° C. / 1.2 kg is 8-20 g / 10 min.
[0014] Furthermore, the ABS resin has a weight average molecular weight of 120,000-160,000, a rubber content of 5-30%, an acrylonitrile content of 20-30%, a styrene content of 40-70%, and a melt index of 10-15 g / min at 200° C. / 1.2 kg.
[0015] Furthermore, the SAN rigid organic particles are styrene-acrylonitrile copolymers with a density of 1.07 g / cm 3 The melt index at 220℃ / 1.2kg is 2.9g / 10min.
[0016] Furthermore, the modified nano-MgO is nano-MgO modified by silane coupling agent KH570.
[0017] Another object of the present invention is achieved by the following technical solution: A method for preparing a scratch-resistant PC material, comprising the following steps:
[0018] S1. Preparation of modified nano-MgO: Add nano-MgO powder to a silane coupling agent modified solution, heat to 60-85°C, react for 4-6 hours, stand for stratification to obtain a precipitate, wash the precipitate with anhydrous ethanol for 3-5 times, dry at 60-70°C for 20-24 hours to obtain modified nano-MgO.
[0019] S2, adding PC resin, ABS resin, SAN rigid organic particles and modified nano-MgO into a high-speed mixer and mixing them evenly;
[0020] S3, passing the mixture obtained in step S2 through a twin-screw extruder, and performing melt blending and extrusion granulation to obtain a scratch-resistant PC material PC / SAN / ABS.
[0021] Furthermore, the silane coupling agent modified solution in step S1 is obtained by mixing distilled water, anhydrous ethanol and KH570 in a volume ratio of 1:99:3;
[0022] The dosage ratio of nano-MgO powder and silane coupling agent modified solution is 1g:20mL.
[0023] Furthermore, in step S2, the rotation speed of the high-speed mixer is 100-300 r / min, and the mixing time is 10-30 min.
[0024] Furthermore, in step S3, the extrusion temperature of the twin-screw extruder is controlled to be 170-230° C., the screw speed is 200-500 rpm, and the pressure is 2-3 MPa.
[0025] Beneficial effects of the present invention:
[0026] (1) The scratch-resistant PC material PC / SAN / ABS prepared by the present invention overcomes the shortcomings of the prior art and has excellent scratch resistance as well as excellent strength and toughness.
[0027] (2) During the preparation of PC / SAN / ABS by the present invention, after the modified nano-MgO is added, the main wear mechanism of the PC material is transformed into fatigue wear, and the wear resistance is improved. The interface bonding between the surface-modified nano-particle filler and the matrix PC resin is strengthened, thereby improving the scratch resistance of the PC material.
[0028] (3) In the process of preparing PC / SAN / ABS of the present invention, the addition of modified nano-MgO improves the compatibility of the PC / SAN / ABS system. Since ABS resin and SAN rigid organic particles have good compatibility, the simultaneous addition of modified nano-MgO, ABS resin and SAN rigid organic particles can enhance the interaction between the SAN particles and the matrix PC resin in the PC / SAN / ABS system, so that the SAN rigid organic particles can better play the role of strengthening and toughening. DETAILED DESCRIPTION
[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Example 1
[0031] This embodiment provides a scratch-resistant PC material, characterized by comprising the following raw materials in parts by weight:
[0032] PC resin: 80 parts,
[0033] ABS resin: 5 parts,
[0034] SAN rigid organic particles: 10 parts,
[0035] Modified nano-MgO: 3 parts.
[0036] A method for preparing a scratch-resistant PC material comprises the following steps:
[0037] S1. Preparation of modified nano-MgO: distilled water, anhydrous ethanol and KH570 were mixed in a volume ratio of 1 mL:99 mL:3 mL to obtain a silane coupling agent modified solution, 5 g of nano-MgO powder was added to 100 mL of the silane coupling agent modified solution, the temperature was raised to 70°C, the reaction was performed for 6 h, and the precipitate was obtained by standing and layering. The precipitate was washed with anhydrous ethanol for 5 times, and dried at 60°C for 24 h to obtain modified nano-MgO.
[0038] S2, weighing PC resin, ABS resin, SAN rigid organic particles and modified nano-MgO according to the above weight ratio, adding them into a high-speed mixer with a rotation speed of 300r / min and mixing for 30min;
[0039] S3, setting the extrusion temperature of the twin-screw extruder to 220° C., the screw speed to 300 rpm, and the pressure to 2 MPa, passing the mixture obtained in step S2 through the twin-screw extruder, and obtaining the scratch-resistant PC material PC / SAN / ABS through melt blending and extrusion granulation.
[0040] Example 2
[0041] The difference between this embodiment and embodiment 1 is that the "ABS resin: 5 parts" in the raw material is changed to "ABS resin: 10 parts"; the other raw materials and preparation process remain the same as those in embodiment 1.
[0042] Example 3
[0043] The difference between this embodiment and embodiment 1 is that the "ABS resin: 5 parts" in the raw material is changed to "ABS resin: 15 parts"; the other raw materials and the preparation process remain the same as those in embodiment 1.
[0044] Example 4
[0045] The difference between this embodiment and embodiment 2 is that the "SAN rigid organic particles: 10 parts" in the raw materials is changed to "SAN rigid organic particles: 15 parts"; the other raw materials and preparation process remain the same as those in embodiment 1.
[0046] Example 5
[0047] The difference between this embodiment and embodiment 2 is that the "SAN rigid organic particles: 10 parts" in the raw materials is changed to "SAN rigid organic particles: 20 parts"; the other raw materials and preparation process remain the same as those in embodiment 1.
[0048] Example 6
[0049] Compared with Example 4, the difference between this example is that the "modified nano-MgO: 3 parts" in the raw material is changed to "modified nano-MgO: 5 parts"; the other raw materials and preparation process remain the same as those in Example 1.
[0050] Example 7
[0051] Compared with Example 4, the difference between this example is that the "modified nano-MgO: 3 parts" in the raw material is changed to "modified nano-MgO: 7 parts"; the other raw materials and preparation process remain the same as those in Example 1.
[0052] The amounts of raw materials used in Examples 1 to 7 are shown in Table 1:
[0053] Table 1
[0054] Weight PC resin ABS resin SAN rigid organic particles Modified Nano-MgO Example 1 80 5 10 3 Example 2 80 10 10 3 Example 3 80 15 10 3 Example 4 80 10 15 3 Example 5 80 10 20 3 Example 6 80 10 15 5 Example 7 80 10 15 7
[0055] Comparative Example 1
[0056] This comparative example is different from Example 6 in that the raw materials are changed to include the following raw materials in parts by weight:
[0057] PC resin: 80 parts,
[0058] ABS resin: 10 parts,
[0059] SAN rigid organic particles: 20 parts; the remaining raw materials and preparation process remain the same as those in Example 6.
[0060] Comparative Example 2
[0061] This comparative example is different from Example 6 in that the raw materials are changed to include the following raw materials in parts by weight:
[0062] PC resin: 80 parts,
[0063] SAN rigid organic particles: 25 parts,
[0064] Modified nano-MgO: 5 parts; the remaining raw materials and preparation process remain the same as those in Example 6.
[0065] The raw materials obtained from the above-mentioned Examples 1 to 7 and Comparative Examples 1-2 were fully dried and then injected into standard specimens using an injection molding machine as test samples for scratch resistance and mechanical properties tests. The scratch resistance test method is to use a scratch tester to evaluate the degree of scratching: a mechanically driven scraper is used to scrape a segmented pattern on the surface of the test sample, and each scraper is scraped only once in one direction, and then a colorimeter is used to measure the color deviation △E compared to the unscratched surface; the sample is subjected to a tensile strength test and a break elongation test in accordance with the national standard GB / T1040.1-2018; the results are shown in Table 2:
[0066] Table 2
[0067] Test items Color difference after scratching △E Tensile strength(MPa) Elongation at break (%) Example 1 0.36 62.8 108 Example 2 0.32 64.2 117 Example 3 0.37 62.6 107 Example 4 0.26 65.0 121 Example 5 0.33 64.1 116 Example 6 0.21 67.2 131 Example 7 0.27 64.9 120 Comparative Example 1 0.46 58.2 96 Comparative Example 2 0.42 58.6 98
[0068] It can be seen from Table 2 that compared with Example 2, Example 2 has better scratch resistance, strength and toughness than Example 1 and Example 3. It can be concluded that the amount of ABS resin should not be too low or too high, because if the amount is too low, the high strength and toughness of the ABS resin itself cannot play a significant role, and if the amount is too high, the compatibility of the PC / SAN / ABS system will be reduced.
[0069] Compared with Example 4, Example 4 has better strength and toughness. It can be concluded that the dosage of SAN rigid organic particles should not be too low or too high, because too low dosage cannot achieve a good reinforcement and toughening effect, and too high dosage will cause the SAN rigid organic particles to become larger in size in the PC / SAN / ABS system, resulting in stress concentration. The microcracks induced by stress concentration cause the blend to break prematurely during the stretching process, thereby reducing the reinforcement and toughening effect of the SAN rigid organic particles.
[0070] Compared with Example 6, Example 6 has better scratch resistance. It can be concluded that the amount of modified nano-MgO should not be too low or too high. When the amount is too small, the content of nanoparticles per unit volume is small, and the scratch resistance enhancement effect of the PC / SAN / ABS system is not obvious; when the amount added is too much, the nanoparticles will agglomerate, resulting in uneven dispersion. The reason for the agglomeration is that although the silane coupling agent can reduce the surface energy of nano-magnesium oxide to a certain extent, the modification process is incomplete, and some nanoparticles still retain a high surface energy on the surface, thereby inducing agglomeration. The large agglomerates on the surface caused by the agglomeration occupy the position of the matrix in the PC / SAN / ABS system, which are easily scraped away during scratching, resulting in poor scratch resistance.
[0071] Compared with Example 1, the scratch resistance, strength and toughness of Comparative Examples 1 and 2 are worse. The reason is that: since the nanoparticles of modified nano-MgO have a very high specific surface area, when they are added to the PC / SAN / ABS system, the components in the system will be strongly adsorbed to the solid surface, which can ensure a strong interface interaction between the polymer matrix and the nanoparticles, thereby improving the compatibility of the PC / SAN / ABS system and enhancing the scratch resistance; and since ABS resin and SAN rigid organic particles have good compatibility, the simultaneous addition of modified nano-MgO, ABS resin and SAN rigid organic particles can enhance the interaction between the SAN particles and the matrix PC resin in the PC / SAN / ABS system, so that the SAN rigid organic particles can better play the role of strengthening and toughening.
[0072] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0073] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A scratch-resistant PC material, characterized in that: The invention comprises the following raw materials in parts by weight: PC resin: 80 parts, ABS resin: 5-15 parts, SAN rigid organic particles: 10-20 parts, Modified nano-MgO: 3-7 parts.
2. The scratch-resistant PC material according to claim 1, characterized in that: The PC resin is a bisphenol A polycarbonate resin, and has a melt index of 8-20 g / 10 min at 300° C. / 1.2 kg.
3. The scratch-resistant PC material according to claim 1, characterized in that: The ABS resin has a weight average molecular weight of 120,000-160,000, a rubber content of 5-30%, an acrylonitrile content of 20-30%, a styrene content of 40-70%, and a melt index of 10-15 g / min at 200° C. / 1.2 kg.
4. The scratch-resistant PC material according to claim 1, characterized in that: The SAN rigid organic particles are styrene-acrylonitrile copolymers with a density of 1.07 g / cm 3 The melt index at 220℃ / 1.2kg is 2.9g / 10min.
5. The scratch-resistant PC material according to claim 1, characterized in that: The modified nano-MgO is nano-MgO modified by silane coupling agent KH570.
6. A method for preparing a scratch-resistant PC material according to any one of claims 1 to 5, characterized in that: The steps include: S1. Preparation of modified nano-MgO: adding nano-MgO powder to a silane coupling agent modified solution, heating to 60-85°C, reacting for 4-6 hours, standing to separate layers to obtain a precipitate, washing the precipitate with anhydrous ethanol for 3-5 times, and drying at 60-70°C for 20-24 hours to obtain modified nano-MgO; S2, adding PC resin, ABS resin, SAN rigid organic particles and modified nano-MgO into a high-speed mixer and mixing them evenly; S3, passing the mixture obtained in step S2 through a twin-screw extruder, and performing melt blending and extrusion granulation to obtain a scratch-resistant PC material PC / SAN / ABS.
7. The method for preparing a scratch-resistant PC material according to claim 6, characterized in that: The silane coupling agent modified solution in step S1 is obtained by mixing distilled water, anhydrous ethanol and KH570 in a volume ratio of 1:99:3; The dosage ratio of nano-MgO powder and silane coupling agent modified solution is 1g:20mL.
8. The method for preparing a scratch-resistant PC material according to claim 6, characterized in that: The rotation speed of the high-speed mixer in step S2 is 100-300 r / min, and the mixing time is 10-30 min.
9. The method for preparing a scratch-resistant PC material according to claim 6, characterized in that: The twin-screw extruder in step S3 is controlled to have an extrusion temperature of 170-230° C., a screw speed of 200-500 rpm, and a pressure of 2-3 MPa.
